Sarekat Islam sebagai Gerakan Sosial: Dari Gerakan Ratu Adil ke Sosialisme Islam - Syaidina Sapta Wilandra; Imas Emalia (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta, 2022)
This article discusses how Sarekat Islam (SI) became a representation of the social movements of the indigenous people in the Dutch East Indies. This research uses the historical method with a sociological approach. Furthermore, this study uses resource mobilization theory in social movements to see the development of thought patterns and movements in SI. The results of this study indicate that, at first, for the indigenous people of SI, it was considered a manifestation of the Ratu Adil movement, where the leaders were considered to have charismatic personalities who would lead them to escape the misery of life. However, this assumption later changed, not only because the leaders of the SI rejected Ratu Adil's assumption but also because the SI itself began to develop a more rational and modern thought, namely socialism and Islamic reformism, in response to conditions in the Dutch East Indies, which eventually realizing the development of ideology and movement within the SI. Socialism-Marxism (communism), which is fundamentally contrary to Islam, made SI eventually split up. Many conflicts occur between the camp that adheres to communism with the anti-communism camp. The peak was when SI began to expressly rid itself of elements of communism through party discipline in 1921.Artikel ini membahas bagaimana Sarekat Islam (SI) menjadi representasi dari gerakan sosial rakyat pribumi di Hindia Belanda. Penelitian ini mengunakan metode sejarah dengan pendekatan sosiologi. Lebih lanjut penelitian ini menggunakan teori mobilisasi sumber daya dalam gerakan sosial untuk melihat perkembangan pola pemikiran dan gerakan di SI. Hasil Penelitian ini menunjukkan bahwa pada awalnya, bagi rakyat pribumi SI dianggap sebagai wujud dari gerakan Ratu Adil dimana para pemimpinnya dianggap memiliki kharismatik yang akan memimpin mereka agar lepas dari kesengsaraan hidup. Namun anggapan ini kemudian berubah, bukan hanya karena para pemimpin SI menolak anggapan Ratu Adil itu, namun juga karena di dalam Sarekat Islam sendiri mulai berkembang sebuah pemikiran yang lebih rasional dan modern yakni sosialisme serta reformisme Islam dalam merespon kondisi di Hindia Belanda, yang akhirnya mewujudkan perkembangan ideologi dan gerakan di dalam SI. Paham sosialisme-marxisme (komunisme) yang bertentangan dasar dengan Islam membuat SI akhirnya terpecah-belah. Banyak konflik terjadi antara kubu yang menganut komunisme dengan kubu yang anti komunisme. Puncaknya yakni ketika SI mulai secara tegas membersihkan diri dari unsur komunisme melalui disiplin partai pada 1921.